8 - Book Review/Critique de livre: Agony In Nation-State Building/Agonie dans construction de la nation - Olajide Oloyede (African Sociological Review, 2015)
A Review of Citizenship between Empire and Nation: Remaking France and French Africa, 1945-1960 Frederick Cooper, Princeton, 493pp, 2014, ISBN 978-0-691-16131-0